ANALISIS KARAKTERISTIK RESPONDEN DAN ATRIBUT PERJALANAN TERHADAP PEMILIHAN MODA ANGKUTAN UMUM RUTE BANDA ACEH – TAPAKTUAN - Andrian Andrian; Renni Anggraini; Sugiarto Sugiarto (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2019)
The variance of transport modes may affect decision of mode choices for user to travel between the cities. Differences of characteristic transport modes add some value for the user in mode choices. Banda Aceh as a capital city of Aceh became the vital point as the center activities of Aceh province. Distibution of commodites and services is linked between Banda Aceh and the other cities in Aceh province, an example  with Tapaktuan which in the between south-west road of Aceh province as distibution of commodites and services from and towards Banda Aceh. The purposes of this study aim for the analysis of needs each public transport modes through the development model  of transport mode choices minibus with ac and minibus non ac. Data for this study collected by survey and questionnaires. Questionnaires designed with stated preference method. Development of model performed with software named SPSS 25 as each of transportation mode used as a comparison (base outcome). Model-based discrete choice model analyzed by binomial logit models approach. The results of the surveys shown the percentage modes choice for minibus ac = 62,5% or 275 respondents and minibus non ac = 37,5% or 165 respondents. The probability value based by respondent’s demographic shown P(minibus ac) = 66,9% and P(minibus non ac) = 33,1%, The probability value based by travel’s attribute shown P(minibus ac) = 57,1% and P(minibus non ac) = 42,9%.